The nature of the catalytically active species in olefin dioxygenation with PhI(OAc)2: metal or proton? - Kang, Yanbiao; Gade, Lutz H. (Journal of the American Chemical Society, 2011)
Evidence for the protiocatalytic nature of the diacetoxylation of alkenes using PhI(OAc)2 as oxidant is presented. Systematic studies into the catalytic activity in the presence of proton-trapping and metal-complexing agents indicate that protons act as catalysts in the reaction. Using triflic acid as catalyst, the selectivity and reaction rate of the conversion is similar or superior to most efficient metal-based catalysts. Metal cations, such as Pd(II) and Cu(II), may interact with the oxidant in the initiation phase of the catalytic transformation; however, 1 equiv of strong acid is produced in the first cycle which then functions as the active catalyst. Based on a kinetic study as well as in situ mass spectrometry, a mechanistic cycle for the proton-catalyzed reaction, which is consistent with all experimental data presented in this work, is proposed.